1H-Benzimidazol-2-ylmethyl phenyl ether - Hassan, N.D.; Tajuddin, Hairul Anuar; Abdullah, Z.; Ng, S.W. (International Union of Crystallography, 2009)
There are two molecules in the asymmetric unit of the title compound, C(14)H(10)N(2)O: the dihedral angles between their aromatic ring planes are 47.4 (4) and 46.8 (3)degrees. In the crystal structure, molecules are linked by N-H center dot center dot center dot N hydrogen bonds from the secondary nitrogen N-H donor to the tertiary N-atom acceptor of a symmetry- related neighbour, resulting in hydrogen- bonded chains. The two independent chains both propagate in 100.